INFORMATION AND COMMUNICATION TECHNOLOGIES: NEW SUPPORTS FOR LITERATURE EDUCATION - Branco, Marta Roque [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2017)
This article aims at discussing the importance of technological resources in the educational environment as a strategy in the training of readers of texts and the world. To that end, the teacher's posture and role will be approached in the face of these new resources, the benefits of the technologies for the educational process and the importance of the teacher's reading practices within this process. There are also some possibilities/suggestions of virtual environments for the teaching of literature involving children. In this path, authors such as Ribeiro (2015), Leal (2006), Fernandes (2011) and Barreto (2001), among others, will help in the discussion to which the work is proposed and in the conclusion that the simple adoption of technologies does not promote changes in the teaching-learning process. For more effective results, it is necessary to question the traditional didactics and a redefinition of the teacher's role and its interaction with the contents, methodologies and with the students.
Keywords: educational practices; technological resources; training of readers